TEACHER MOTIVATION DOES NOT STAY AT MAK IHYA ULUMIDDIN BANYUWANGI DISTRICT - FITRIYAN MUNAWWIR (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2018)
This study is to determine the level of motivation of teachers not to carry out teaching and learning. The method used is a qualitative method by emphasizing case studies. The results show that the role of the teacher as one of the components in teaching and learning activities (KBM), has a role that determines the success of learning. Seeing the importance of the teacher's role in the education process and at the same time as the party responsible for implementing the education process in schools, teachers are required to have expertise, responsibility and a soul willing to provide social services above personal interests. But amidst the many demands on the teaching profession, many problems are experienced by teachers, especially Non-permanent Teachers (GTT), which revolve around issues of welfare and clarity of employment status.